2017
DOI: 10.1056/nejmoa1612674
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib or Platinum–Pemetrexed in EGFR T790M–Positive Lung Cancer

Abstract: Osimertinib had significantly greater efficacy than platinum therapy plus pemetrexed in patients with T790M-positive advanced non-small-cell lung cancer (including those with CNS metastases) in whom disease had progressed during first-line EGFR-TKI therapy. (Funded by AstraZeneca; AURA3 ClinicalTrials.gov number, NCT02151981 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

121
2,446
15
46

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,873 publications
(2,747 citation statements)
references
References 25 publications
121
2,446
15
46
Order By: Relevance
“…However, the use of mandatory biopsies throughout a patient's treatment is expected to increase as biomarker-driven drug approvals become the norm [16]. Osimertinib is a third-generation, EGFR-TKI that potently and selectively inhibits both EGFR sensitizing and EGFR T790M resistance mutations [5,17,18]. Based on positive results from the AURA trial program and FLAURA first-line study, osimertinib is recommended in the US as a first-line treatment option for patients with EGFR mutation-positive advanced NSCLC and as a second-line treatment for patients with T790M-positive NSCLC following disease progression on a first-line EGFR-TKI therapy (erlotinib, gefitinib, or afatinib) [12,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of mandatory biopsies throughout a patient's treatment is expected to increase as biomarker-driven drug approvals become the norm [16]. Osimertinib is a third-generation, EGFR-TKI that potently and selectively inhibits both EGFR sensitizing and EGFR T790M resistance mutations [5,17,18]. Based on positive results from the AURA trial program and FLAURA first-line study, osimertinib is recommended in the US as a first-line treatment option for patients with EGFR mutation-positive advanced NSCLC and as a second-line treatment for patients with T790M-positive NSCLC following disease progression on a first-line EGFR-TKI therapy (erlotinib, gefitinib, or afatinib) [12,19].…”
Section: Discussionmentioning
confidence: 99%
“…Although tumor tissue samples remain the gold standard for cancer mutation testing, novel methods of testing are emerging that are less invasive, including those based on cytology samples and ctDNA which should be considered for patients who are ineligible for a tissue biopsy. Various studies support the use of plasma ctDNA samples for the detection of EGFR mutations at diagnosis of NSCLC, including data from the recent AURA (AURA extension, AURA2, and AURA3) and FLAURA studies [18,31,32,17]. The phase I AURA post-hoc analysis (NCT01802632) found that, in patients with advanced NSCLC and EGFR T790M-positive status (according to central tumor genotyping), the sensitivity of plasma ctDNA samples for the detection of T790M was 70% [32].…”
Section: Discussionmentioning
confidence: 99%
“…Waiting for the results in the T790M-positive cohort included in the BLOOM study, osimertinib has already shown high activity in patients with CNS disease harboring T790M mutation enrolled in two phase II studies (Goss, 2017), likely due to its greater penetration of animal models' BBB compared to other TKIs, gefitinib, rociletinib, or afatinib (Ballard et al, 2016). Furthermore the recent results of the AURA 3 trial demonstrated a significant survival benefit of osimertinib over platinum-chemotherapy in 144 T790M-positive patients with CNS metastasis at baseline, suggesting it as a very effective drug for these patients (Mok et al, 2017). Recently the results of the first prospective randomized trial comparing EGFR-TKI icotinib vs WBRT ± chemotherapy in EGFR-mutated asian NSCLC patients with BM, have shown a significant superiority of TKI in terms of both intracranial and systemic RR, as well as intracranial and systemic PFS, together with a lower incidence of severe treatment-related AEs .…”
Section: Activity Against Brain Metastasismentioning
confidence: 99%
“…The AURA1 study has first shown an impressive ORR: 60%, disease control rate (DCR): 95%, PFS: 9.6 months with minimal side effects in the subgroup of patients with 790M mutation (Skoulidis and Papadimitrakopoulou, 2017), leading to the fast-track approval by regulatory authorities for the treatment of patients who develop resistance to first-generation TKIs and were T790 M positive. The results of the phase III randomized AURA3 trial, comparing osimertinib vs platinum-pemetrexed chemotherapy in this setting of patients have been recently reported at the last World Conference on Lung Cancer (WCLC) 2016 and simultaneously published on the New England Journal of Medicine (NEJM) (Mok et al, 2017). The study met its primary endpoint showing a significant longer median PFS in patients receiving osimertinib compared to platinum chemotherapy (PFS: 10.1 vs 4.4 months; HR: 0.30, 95%CI: 0.23-0.41), including also the subgroup of patients with brain metastasis (HR: 0.32, 95%CI: 0.21-0.49).…”
Section: New Generation Egfr-tkismentioning
confidence: 99%
“…However, the efficacy of osimertinib treatment for patients with a poor PS remains uncertain. As only few patients in the osimertinib group reported grade ≥3 adverse events in the AURA3 clinical trial (8), the administration of osimertinib was considered to be a viable option for our patient, despite her poor PS. The disturbance of consciousness gradually improved, despite only 2 days of treatment with 80 mg osimertinib.…”
mentioning
confidence: 97%